Konkurzní řízení firmy - Izáková, Eva (Univerzita Pardubice, 2006)
Diplomová práce Konkursní řízení firmy se zabývá tématem konkursů v České republice podle platné právní úpravy, zákona č. 328/1991 Sb., o konkursu a vyrovnání. Cílem práce je popsat postup průběhu konkursního řízení, porovnat počty konkursů v ČR a ve světě a nakonec popsat konkrétní případ konkursního řízení firmy DESMON s.r.o. s cílem určit možné příčiny, které způsobily úpadek podnikatelského subjektu.

Thesis Bankruptcy proceedings of the firma deals with the subject of bankrupts in the Czech Republic according to valid legal regulation, Act No. 328/1991, on bankruptcy and satisfaction. The purpose is to describe the process of course of bankruptcy proceedings, to compare number of bankruptcy in the Czech Republic and in the world and in the end to describe the concrete case of the bankruptcy proceedings of the firma DESMON Ltd. of purpose to identify the feasible factors, which caused the bankruptcy of the business subject.
Bankruptcy proceedings of the firma
Keywords: debtors; insolvency; trading companies; bankruptcy proceedings; active debts; liabilities; dlužníci; insolvence; obchodní společnosti; konkursní řízení; Pohledávky; závazky